High-throughput screening methods in toxicity testing - Steinberg, Pablo (Wiley, 2013)
"High-throughput assays are part of a paradigm shift, to more cost-effective and reliable methods, in the testing of chemical and drug safety. This book covers methods, data generation, data analysis, and applications in risk assessment for major toxicological assays to help toxicologists apply and understand the benefits and limits of high-throughput testing assays. Each chapter describes method principles and includes detailed information on data generation, data analysis, and applications in risk assessment. The topic is especially timely given Europe's REACH legislation and the US National Research Council"--